1999
DOI: 10.4141/s99-035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil redistribution on soil properties in a cultivated Solonetzic-Chernozemic landscape of southwestern Saskatchewan

Abstract: . 1999. Effects of soil redistribution on soil properties in a cultivated Solonetzic-Chernozemic landscape of southwestern Saskatchewan. Can. J. Soil Sci. 79: 593-601. Although approximately 1.3 million ha of mixed Solonetzic -Chernozemic landscapes are cultivated in Saskatchewan, little information is available on the effects that agriculture has had on the quality of these soils. At our research site in southwestern Saskatchewan a clear landscape-scale pattern of soil distribution occurred. Regosolic and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Only the participating sites were able to support brush vegetation. Ultimately, the fact that Solonetzic soils are often found in association with Chernozemic soils over small spatial scales (Miller & Brierley, ; Pennock et al, ) results in a particularly heterogeneous landscape (Carter & Pearen, ; Pennock et al, ; Sandoval & Reichman, ). For instance, Carter and Pearen () found that some physical properties of Solonetzic soils, such as the thickness of the A horizon, exhibit little spatial dependence at distances greater than 5 m. Similarly, Sandoval and Reichman () report that infiltration rates into Solonetzic soils are also highly variable within short distances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only the participating sites were able to support brush vegetation. Ultimately, the fact that Solonetzic soils are often found in association with Chernozemic soils over small spatial scales (Miller & Brierley, ; Pennock et al, ) results in a particularly heterogeneous landscape (Carter & Pearen, ; Pennock et al, ; Sandoval & Reichman, ). For instance, Carter and Pearen () found that some physical properties of Solonetzic soils, such as the thickness of the A horizon, exhibit little spatial dependence at distances greater than 5 m. Similarly, Sandoval and Reichman () report that infiltration rates into Solonetzic soils are also highly variable within short distances.…”
Section: Discussionmentioning
confidence: 99%
“…Soils belonging to the Soloneztic Order are often referred to more generally as sodic soils, and hereafter, we use the terms interchangeably. In the prairies, Solonetzic soils are typically found in catenas with soils of the Chernozemic Order (Miller & Brierley, ; Pennock et al, ). Solonetzic soils form from salinized parent material, rich in sodium salts (Pawluk, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catenary distribution of soil properties and taxa along hillslopes in hummocky and undulating Prairie landscapes has been often studied, in part because elsewhere it is rare to see members of three soil orders occurring within tens of meters of each other; indeed in Solonetzic-Chernozemic landscapes we can observe members of four orders over the same distance (Pennock et al 1999). The occurrence of different B horizon features, and the consequent occurrence of different subgroups along the catenary sequence, has been well established across these studies (Figs.…”
Section: Catenary Relationships: Topographical Position and The Subgroups Of The Chernozemsmentioning
confidence: 99%